Nonlinear sprint performance differentiates professional from young soccer players - Cardoso de Araujo, M.; Baumgart, C.; Freiwald, J.; Hoppe, M. W. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Linear and nonlinear sprinting activities are relevant physical capacities in soccer. This study aimed to compare linear and nonlinear sprint performance between professional and young soccer players, and to investigate relationships between both sprint types. METHODS: Sixty-eight German male elite field soccer players were grouped based on age as professional (PRO, N.=20), under-23 (U23, N.=16), under-19 (U19, N.=18), and under-17 (U17, N.=14). All players were tested for 30-m linear (split-times at 5, 10, and 20 m) and 22-m nonlinear sprint performance. RESULTS: In linear sprint, PRO players were moderately to very largely faster than U17 players at all distances and also than U19 players at 20 m (effect size [ES]=0.90-2.06, P=0.04). U23 players were moderately to largely faster than U17 players at 5 and 10 m (ES=0.93-1.74, P=0.04). In nonlinear sprint, PRO players were moderately to largely faster than all other groups (ES=1.04-1.84, P=0.02). Moderate to large correlations were found between linear and nonlinear sprint performance for all players (r=0.48-0.50, P<0.01). Within groups, moderate to large correlations were evident only for PRO at 5-20 m (r=0.45-0.61, P=0.05) and U23 at 30 m (r=0.55, P=0.03). CONCLUSIONS: The findings indicate that nonlinear sprint performance is a key physical capacity in professional soccer. Therefore, training programs should focus to increase this capacity in younger players. Furthermore, linear and nonlinear sprint performance should be independently tested and trained in elite players.